ChemInform Abstract: Above‐Room‐Temperature Ferroelastic Phase Transition in a Perovskite‐Like Compound [N(CH3)4][Cd(N3)3]. Issue 15 (15th April 2014) - Du, Zi‐Yi; Zhao, Ying‐Ping; Zhang, Wei‐Xiong; Zhou, Hao‐Long; He, Chun‐Ting; Xue, Wei; Wang, Bao‐Ying; Chen, Xiao‐Ming
Abstract Block‐shaped single crystals of the new title compound are synthesized by slow evaporation of the filtrate of an aqueous mixture of Cd(NO3)2, NaN3, and Me4NBr in the ratio of 1:12:6 (20 °C, 55% yield).